Impacto del liderazgo transformacional en el clima organizacional de la Empresa Constructora H2O Consulting S.A.S. (2023)
The research was based on establishing the impact of transformational leadership on the organizational climate of the construction company H2O Consulting S.A.S; To determine and evaluate the situation of the organizational climate, survey-like instruments were used with variables defined through closed and structured questions, in such a way that the participant is offered alternative answers. To measure the perception of leadership styles and the relationship with the organizational climate, the focus group was used as a tool, which developed a guide format with open, circular and reflective questions.